Feedback regulation of rRNA and tRNA synthesis and accumulation of free ribosomes after conditional expression of rRNA genes. - Gourse, R L (1985)
We have constructed a conditional rRNA gene expression system by fusing a plasmid-encoded rrnB operon to the lambda PL promoter/operator. It was thereby possible to study the events that lead to the regulation of chromosomal rRNA and tRNA synthesis after overproduction of rRNA. rRNA induction resulted in a 2-fold increase in 30S and 50S free ribosomal subunits, whereas the polysome fraction was unaffected. Overproduction of rRNA and "free" ribosomes produced a large repression of rRNA and tRNA synthesis from chromosomal genes and a smaller increase in the concentration of guanosine tetraphosphate. These results lend support to the ribosome feedback regulation model: rRNA and tRNA operons are negatively regulated, either directly or through some intermediate, by free, nontranslating ribosomes.